2007
DOI: 10.3892/or.18.5.1269
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces pro-apoptotic endoplasmic reticulum stress in human colon cancer cells

Abstract: Abstract. Resveratrol (3,4',5 tri-hydroxystilbene), a naturally occurring polyphenolic compound highly enriched in grapes and red wine, has been shown to induce anti-proliferation and apoptosis of human cancer cell lines. Resveratrol-induced dose-dependent apoptotic cell death in colon carcinoma cells, was measured by FACS analysis. Treatment of HT29 human colon carcinoma cells with resveratrol was found to induce a number of signature ER stress markers; phosphorylation of eukaryotic initiation factor-2α (eIF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 26 publications
4
49
0
Order By: Relevance
“…Strikingly, the altered epigenetic acetylation status did not affect Atg7, which points to a regulatory mechanism that protects Atg genes from hypoacetylation [171]. Resveratrol-induced autophagy might also involve the induction of ER stress as resveratrol has been shown to induce several ER stress markers, e.g., eukaryotic translation initiation factor 2α (eIF2α) phosphorylation, X-box-binding protein 1 splicing and CHOP (C/EBP homologous protein) expression [172]. In line with the notion that autophagy is important in slowing down the ageing process, a decline in formation and elimination of autophagosomes is often observed in ageing cells [173].…”
Section: Autophagy and Ageingmentioning
confidence: 99%
“…Strikingly, the altered epigenetic acetylation status did not affect Atg7, which points to a regulatory mechanism that protects Atg genes from hypoacetylation [171]. Resveratrol-induced autophagy might also involve the induction of ER stress as resveratrol has been shown to induce several ER stress markers, e.g., eukaryotic translation initiation factor 2α (eIF2α) phosphorylation, X-box-binding protein 1 splicing and CHOP (C/EBP homologous protein) expression [172]. In line with the notion that autophagy is important in slowing down the ageing process, a decline in formation and elimination of autophagosomes is often observed in ageing cells [173].…”
Section: Autophagy and Ageingmentioning
confidence: 99%
“…80 Park et al reported that resveratrol induces endoplasmic reticulum stress in HT 29 cells as seen from the upregulation of glucose-regulated protein (GRP)-78 and other markers of ER stress. 81 Resveratrol also induces CCAAT/ enhancer-binding protein-homologous protein (CHOP) in HT 29 cells 82 and inhibits the telomerase activity in HT-29 and WiDr cells. 83 Another report by Mohan et al suggested that resveratrol treatment activates caspase-2, which in turn triggers mitochondrial apoptotic events by inducing conformational changes in Bax/ Bak with subsequent release of cytochrome c, apoptosis-inducing factor and endonuclease G. 84 Resveratrol also produced growth inhibition and G 2 /M arrest in Caco-2 cells.…”
Section: Gastrointestinal and Colorectal Cancermentioning
confidence: 99%
“…1,2 Resveratrol inhibits cancer cell growth in many cell lines, including cancers of the lung, prostate, colon, breast and ovaries. [3][4][5][6][7][8][9][10][11][12][13][14] Resveratrol also reduces tumor incidence in animal models by interfering with carcinogenesis through a wide array of anti-cancer actions. Several animal studies have demonstrated the ability of resveratrol to inhibit prostate cancer development by downregulating androgen receptors, inducing apoptosis/cell cycle arrest and inhibiting disease progression.…”
mentioning
confidence: 99%